HUBUNGAN ANTARA SELF-COMPASSION DENGAN SELF-CRITICISM PADA DEWASA AWAL YANG TERPAPAR KONTEN PRESTASI DI MEDIA SOSIAL - Maryam Zahra; Raja Oloan Tumanggor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid growth of social media in the digital era has led emerging adults to be increasingly exposed to achievement-oriented content, including academic accomplishments, career success, and personal achievements. Such exposure frequently elicits upward social comparison, which may, in turn, intensify tendencies toward self-criticism. However, self-compassion is widely regarded as a protective factor that can mitigate these negative effects. Therefore, this study aimed to examine the relationship between self-compassion and self-criticism among emerging adults who are exposed to achievement-related content on social media. The participants consisted of 189 individuals aged 18–29 years who actively use social media and have previously encountered achievement-related content. Data were collected online using the Self-Compassion Scale (SCS) and the Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS). Subsequently, data analysis was conducted using Spearman’s correlation. The results revealed a strong and significant negative relationship between self-compassion and self-criticism (ρ = –0.600, p < .001). In other words, higher levels of self-compassion were associated with lower tendencies toward self-criticism. Overall, these findings underscore the crucial role of self-compassion as an important protective factor against the negative psychological impacts of exposure to achievement-related content on social media. Accordingly, this study is expected to serve as a foundation for the development of interventions aimed at enhancing self-compassion in order to strengthen the mental health of emerging adults in the digital era.